Risk factors for screw loosening in patients with adult degenerative scoliosis: the importance of paraspinal muscle degeneration - Wei Wang; Weishi Li; Zhongqiang Chen (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Paraspinal muscle is an important component to maintain spinal stability. But the relationship between the degeneration of paraspinal muscle and postoperative screw loosening in patients with adult degenerative scoliosis has not been studied. The objective of this study was to investigate risk factors for screw loosening in patients with adult degenerative scoliosis, including paraspinal muscle degeneration. Methods We investigated 93 patients with adult degenerative scoliosis who underwent spinal interbody fusion and pedicle screw fixation surgery. The lateral curvature was located in the lumbar spine and the follow-up time was ≥ 2 years. The patients were divided into loosening and non-loosening groups. Screw loosening was defined as a 1-mm or wider circumferential radiolucent line around the pedicle screw. We checked the cross-sectional area of paraspinal muscles, spinopelvic parameters, bone mineral density, number of fusion segment, and other factors. The potential risk factors for screw loosening were investigated by using binary logistical regression analysis. Results Fifty-seven patients showed screw loosening, which is 63.4% of total. Compared with patients in the non-loosening group, the cross-sectional area of erector spinae and psoas major muscle at L5 level were significantly smaller in patients with screw loosening (P < 0.05). Among these factors, the number of fused segments and relative erector spinae total cross-sectional area were independent risk factors for screw loosening. Conclusions The degeneration of paraspinal muscle and the increase of fusion segment were independent factors for screw loosening in patients with adult degenerative scoliosis.